Studi Kasus Pada Pasien Demam Berdarah Dengue - Maria Sumaryati; Rosmiaty Rosmiaty; Wasilah Wasilah (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Background dengue Hemorrhagic Fever is an infectious disease caused by dengue virus and transmitted by Aedes mosquitoes. Dengue virus infection causes high mortality and morbidity throughout the world. The aim is to apply nursing care to clients with Dengue Hemorrhagic Fever which includes assessment, diagnosis, intervention, implementation and evaluation of nursing. Method, the research design used is descriptive using case study methods. Participation used was 1 pediatric patient with a diagnosis of Dengue Hemorrhagic Fever. Results, Nursing problems that arise in the case that I get is hyperthermia associated with the process of dengue virus infection, ineffective airway clearance associated with secretions, and the risk of nutritional imbalance less than the body's needs associated with inadequate nutrient intake due to nausea, vomiting and appetite decreased. After 3 x 24 hours of nursing action, the results of hyperthermia are resolved, the ineffectiveness of the airway clearance is resolved, and the risk of nutritional imbalances is resolved. The data was obtained from interviews, observations, and documentation. In conclusion, the application of nursing care in accordance with the nursing process will achieve good results in accordance with predetermined outcome criteria. Achieving the success of nursing care requires collaboration between the health team, the patient and the patient's family.